Half a Century of Super Bowl Commercials: A Content Analysis of Humorous Advertising Styles - Timamopoulou, Artemis; Hatzithomas, Leonidas; Boutsouki, Christina; Voutsa, Maria C. (My University, 2021)
Humor is an integral part of our everyday reality. It is a source of strength to compete with and face personal and social challenges as well as political disruptions (Berger 2008). Humor is imbedded in every culture (Berger 1987) and an individual’s sense of humor reveals not only aspects of their personality but also their mode of social interaction (Lynch 2002).
Keywords: Humorous commercials; Humor styles; American society